DEVELOPMENT OF NUTRIENT MEDIUM AND CULTIVATION REGIMES OF FOR BACTERIAL CONCENTRATE PRODUCTION - Raskoshnaya T.A.; Semenikhina V.F.; Rozhkova I.V.; Begunova A.V. (Техника и технология пищевых производств, 2016)
Lactobacillus reuteri has been selected in the All-Russia Dairy Research Institute. The mentioned type of lactic acid bacteria possesses a wide spectrum of functional properties thus the development of L.reuteri bacterial concentrate is actual and demanded. The aim of the present investigations is to choose ferment preparation which makes it possible to obtain protein hydrolysates from skimmed milk and whey as the basis for the creation of nutrient medium, to study the impact of some factors (proteolytic ferment dose, hydrolyze duration), to carry out optimization of nutrient medium by different components, and to select the technological regimes (temperature, medium pH, inoculate dose) of L.reuteri cultivation. Four proteolytic ferments (protosubtilin, Alcalase, Neutrase, Protamex) were chosen in the concentration of 0.4% and 3.0%. The hydrolyze process duration was 1.5 and 3 h, the process temperature was 55°C, the active acidity was 7.2 pH units. Investigations on optimization of nutrient medium composition relating to separate components influence (hydrolysate, yeast extract, sucrose, cystein, inulin) on its nutritional value have been conducted. The influence of technological regimes of L.reuteri cultivation (active acidity 5.6-6.6 pH units, cultivation temperature (32-41)°C, inoculate dose from 3% to 8%) on cells accumulation in the medium has been studied. The analyses of the findings showed that the number of cells cultivated on hydrolysate obtained from skimmed milk was higher than that cultivated on hydrolysate obtained from whey. The investigation on the introduced ferment type and dose impact showed that the studied ferments possessed practically similar influence on L.reuteri cells accumulation. The intensity of cells growth became higher with the ferment dose increasing. The optimum nutrient medium composition for L.reuteri cultivation has been determined: hydrolysate - 96.75%, yeast extract - 3% and inulin - 0.25%. The optimum technological regimes for L.reuteri cultivation have been also defined: temperature - 37°C, active acidity - 6.2 pH units, inoculate dose - 6-7%, cultivation period - 6-8 hrs. In this case, the number of cells amounted to 2×10? CFU/cm³.